Comparing eSRT and eCAP measurements in pediatric MED-EL cochlear implant users. (4th May 2018) - Kosaner, Julie; Spitzer, Philipp; Bayguzina, Svetlana; Gultekin, Muammer; Behar, Laurie Arum
Abstract : Introduction : Electrically evoked compound action potentials (eCAP) and electrically evoked stapedius reflexes are the most frequently used objective measurements for programming a cochlear implant (CI) audio processor. Objective methods are particularly beneficial for children and CI users that encounter difficulties in providing feedback. In this study, we compared the threshold and the slope of the eCAP amplitude growth function with the electrically evoked stapedius reflex threshold (eSRT) in pediatric CI users. Furthermore, the duration times required to perform eCAP and eSRT recordings were compared. Methods : During a regular fitting session, 52 pediatric CI users with recordable eSRTs having MED-EL devices (MED-EL GmbH, Innsbruck, Austria) were programmed using the eSRT fitting method. The eCAP thresholds and the slopes of the amplitude growth function were measured across one apical, one medial, and one basal electrode contact. Results : There was a weak to medium correlation between eCAP thresholds and eSRTs. The eCAP threshold profile did not correlate with the eSRT profile. Typically ECAP thresholds were at a lower stimulation charge than eSRTs with only 4/152 being higher. An eCAP threshold was found on 152/156 electrode contacts with eSRTs. On average, the eCAP measurements took 4.2 times longer to record per electrode than eSRT measurements (median durations 35 s vs. 120 s). Conclusion : eSRTs were significantly higher than eCAP thresholds and eSRT and eCAP profiles were generally different from each other reducing the clinical relevance of eCAP testing for setting MCLs across the array. Additionally, the eSRT measurements were faster to record than the eCAP threshold and slope determination measurements.